Effects of major and trace elements from the El Kahfa ring complex on fish: Geological, physicochemical, and biological approaches - Saad, Eman; Hamed, Mohamed; Elshahawy, Abdelnaby M.; Abd El-Aal, Mohamed; Sayed, Alaa El-Din H. (Frontiers in Environmental Science, 2023)
The alkaline rocks are known for enriching rare lithophilic elements, including lithium, uranium, and tin, which negatively impact aquatic life. This study offers an intensive investigation of the influence of alkaline rocks on Nile Tilapia (Oreochromis niloticus). The variation in blood profile, the induction of antioxidant enzymes, morphological erythrocyte, and histological structure have been conducted for the fish after 15 days of exposure to alkaline rocks powder with a dose of 100 μg/L. As a result, there was a pronounced decrease in blood profiles, such as platelets and white blood cell counts. There was a failure in the liver and kidney functions. Moreover, it shows an increase in superoxide dismutase (SOD) and catalase (CAT) activities as antioxidant biomarkers. Also, exposure to alkaline rocks induced DNA mutation and erythrocyte distortion. We concluded that the bulk alkaline rocks induced changes in the hemato-biochemical and antioxidant parameters of Nile tilapia. Additionally, exposure to bulk alkaline rock compounds also caused poikilocytosis and nuclear abnormalities of RBCs. This draws our attention to the seriousness of climatic changes, the erosion of rocks, and their access to water.